(3CUhd GdeQGLYI GdMchejI h JWHjbGJgG HGdefWbI GdYQHjIs - (3CMeO UdGM(B, (3YWjIs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2008)
(3WHjYI GdeQGLYI GdMchejI h WHjYI CHYGO hXjaI CLgRI GdQbGHI GdYdjG, Jbjje COGA CLgRI GdQbGHI GdYdjG aj GdefWbI GdYQHjI, eQGLYI GdaSGO GdMchej h CNjQG eQGLYI GdGOGA GdMchej, GdGWGQ GdYGe deQGLYI GdCOGA GdMchej, JWHjb eHGOF GdeQGLYI GdMchejI Ydi eQGLYI GdCOGA, GdJNWjW deQGLYI GdGOGA h JfajPg h ZYOGO JbQjQ GdeQGLYIs
Keywords: (3GdQbGHI GdeGdjIs; (3GdeMGSHI GdMchejIs; (3GdeSDhdjI GdMchejIs; (3eQGLYI GdMSGHGJs